2018
DOI: 10.1111/scs.12556
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in cancer care: exploring social categories in encounters between healthcare professionals and breast cancer patients

Abstract: There is a need for a greater focus on improving encounters between breast cancer patients and healthcare professionals to ensure that rehabilitation needs are accommodated for among diverse patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Furthermore, studies have shown that HPs tend to use their own preconceptions in assessing patient resources rather than involving the patient, 19,20 that HPs were less likely to offer rehabilitation to patients whom they considered to have fewer resources, 22 and that health discourse emphasizing patients' proactivity and responsibility for their own health favoured the physically and socially more privileged 23 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown that HPs tend to use their own preconceptions in assessing patient resources rather than involving the patient, 19,20 that HPs were less likely to offer rehabilitation to patients whom they considered to have fewer resources, 22 and that health discourse emphasizing patients' proactivity and responsibility for their own health favoured the physically and socially more privileged 23 …”
Section: Introductionmentioning
confidence: 99%